2019
DOI: 10.1016/j.thromres.2019.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Implanted vascular access device related deep vein thrombosis in oncology patients: A prospective cohort study

Abstract: A B S T R A C TBackground: Implanted vascular access devices (IVADs) have significantly improved the management of cancer patients. These patients are at an increased risk of venous thromboembolism and IVADs are a known risk factor. We sought to assess the incidence of IVAD-related upper extremity deep vein thrombosis (IVAD-related UEDVT) associated with BioFlo® IVADs (Angiodynamics, Inc.). Methods: A total of 394 cancer patients were enrolled over 12 months. The primary outcome was the incidence of IVAD-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
(32 reference statements)
0
9
0
1
Order By: Relevance
“…Piran et al (14) reported that the rate of symptomatic venous thrombosis was 4.5%; all implanted ports were inserted via the internal jugular vein without mention of catheter size. Suleman et al (15) reported the rate of TIVAP-related venous thrombosis was 1.29% after implantation of the TIVAP via the internal jugular vein with 8Fanti-thrombogenic polymer catheter. Tabatabaie et al (16) reported that the rate of TIVAP-related venous thrombosis was 1.81% (926/51,049); however, information was not provided regarding the diameter and material of the catheter or access route.…”
Section: Discussionmentioning
confidence: 99%
“…Piran et al (14) reported that the rate of symptomatic venous thrombosis was 4.5%; all implanted ports were inserted via the internal jugular vein without mention of catheter size. Suleman et al (15) reported the rate of TIVAP-related venous thrombosis was 1.29% after implantation of the TIVAP via the internal jugular vein with 8Fanti-thrombogenic polymer catheter. Tabatabaie et al (16) reported that the rate of TIVAP-related venous thrombosis was 1.81% (926/51,049); however, information was not provided regarding the diameter and material of the catheter or access route.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial thrombus weight was used to represent the antiarterial thrombotic activity and measured on Sprague Dawley rat model (male, 240-270 g, each 10) by following the procedure of the literature. 25 In this assay 0.5% CMC-Na (blank control, oral dose: 10 mL/kg) or a suspension of aspirin in 0.5% CMC-Na (positive control, oral dose: 167 µmol/kg) or a suspension of 13-Cys-BBR in 0.5% CMC-Na (oral dose: 66.7 nmol/kg) or a suspension of BBR in 0.5% CMC-Na (parent compound control, oral dose: 66.7 nmol/kg) were given to the rats. 30 min after oral administration the rat was anaesthetized with sodium pentobarbital (80.0 mg/kg, ip), then the right carotid artery and left jugular vein of the rat were separated.…”
Section: Arterial Thrombus Weight Assaymentioning
confidence: 99%
“…Venous thrombus weight was used to represent the anti-venous thrombotic activity and measured on Sprague Dawley rat model (male, 240-270 g, each 12) by following the procedure of the literature. 25 Inferior vena cava (IVC) ligation model was used to evaluate the activity. In brief, rats were orally given 0.5% CMC-Na (blank control, oral dose: 10 mL/kg) or a suspension of warfarin in 0.5% CMC-Na (positive control, oral dose: 4870 nmol/kg) or a suspension of 13-Cys-BBR in 0.5% CMC-Na (oral dose: 66.7 nmol/kg) or a suspension of BBR in 0.5% CMC-Na (parent compound control, oral dose: 66.7 nmol/kg).…”
Section: Venous Thrombus Weight Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Hospital-acquired venous thromboembolism (VTE) has received increasing attention in medical institutions due to its increased morbidity and mortality among hospitalized patients [1][2][3][4] . A number of studies have identi ed several important risk factors for hospital-acquired thrombus, of which CVC is an important risk factor [5][6][7] . Symptomatic CRVT is a special type of hospital-acquired VTE.…”
Section: Introductionmentioning
confidence: 99%